Ring homomorphisms on H(G) - N. R. Nandakumar (International Journal of Mathematics and Mathematical Sciences)
It is shown that a ring homomorphism on H(G), the algebra of analytic functions on a regular region G in the complex plane, is either linear or conjugate linear provided that the ring homomorphism takes the identity function into a nonconstant function.